Strategy for the Generation of Engineered Bone Constructs Based on Umbilical Cord Mesenchymal Stromal Cells Expanded with Human Platelet Lysate - Ingrid Silva-Cote; Mónica Cruz-Barrera; Mariana Cañas-Arboleda; Luz Correa-Araujo; Leidi Méndez; Joanna Jagielska; Bernardo Camacho; Gustavo Salguero (Hindawi Limited, 2019)
Umbilical cord mesenchymal stromal cells (UC-MSC) are promising candidates for cell therapy due to their potent multilineage differentiation, enhanced self-renewal capacity, and immediate availability for clinical use. Clinical experience has demonstrated satisfactory biosafety profiles and feasibility of UC-MSC application in the allogeneic setting. However, the use of UC-MSC for bone regeneration has not been fully established. A major challenge in the generation of successful therapeutic strategies for bone engineering lies on the combination of highly functional proosteogenic MSC populations and bioactive matrix scaffolds. To address that, in this study we proposed a new approach for the generation of bone-like constructs based on UC-MSC expanded in human platelet lysate (hPL) and evaluated its potential to induce bone structures in vivo. In order to obtain UC-MSC for potential clinical use, we first assessed parameters such as the isolation method, growth supplementation, microbiological monitoring, and cryopreservation and performed full characterization of the cell product including phenotype, growth performance, tree-lineage differentiation, and gene expression. Finally, we evaluated bone-like constructs based on the combination of stimulated UC-MSC and collagen microbeads for in vivo bone formation. UC-MSC were successfully cultured from 100% of processed UC donors, and efficient cell derivation was observed at day 14±3 by the explant method. UC-MSC maintained mesenchymal cell morphology, phenotype, high cell growth performance, and probed multipotent differentiation capacity. No striking variations between donors were recorded. As expected, UC-MSC showed tree-lineage differentiation and gene expression profiles similar to bone marrow- and adipose-derived MSC. Importantly, upon osteogenic and endothelial induction, UC-MSC displayed strong proangiogenic and bone formation features. The combination of hPL-expanded MSC and collagen microbeads led to bone/vessel formation following implantation into an immune competent mouse model. Collectively, we developed a high-performance UC-MSC-based cell manufacturing bioprocess that fulfills the requirements for human application and triggers the potency and effectivity of cell-engineered scaffolds for bone regeneration.